INFLUENCE OF ADDITIONAL VIBRATION IMPACT ON THE EFFECTIVENESS OF ELECTRICAL STIMULATION PROCEDURE - M. G. Kiselev; E. I. Labun; P. S. Liutsko (Приборы и методы измерений)
An experimental instrument complex which includes hardware for performing complex procedures using electrical shock massager frictional action was performed. The aim of the study was to influence the additional vibration effect on the efficiency of the procedure of electrostimulation.In order to increase the efficiency of the procedure electrostimulation authors proposed to carry it out with using of massager shock-friction action. The changes of muscular indicator on different stimulation treatments was shown after a series of seven treatments .Results of the processing of the experimental data and its subsequent analysis found that the use of the vibration exposure is accompanied by increase of load parameters in untrained volunteers. The increase in contact area due to decrease in the distance between the nozzle and the axis of rotation of the tumbler body surface, increases the electrical efficiency of the procedure.On the basis of a generalized analysis of data reflecting the effect of inappropriate electrical stimulation, it was established that, in order to achieve the best results, oscillatory systems providing shock-friction mode of its interaction with the skin surface, in particular a shock-frictional massager, were used.